ANALISIS PENGELOLAAN DAN DAMPAK DEBU DI KILANG PADI TERHADAP PEKERJA DI PT. MGS TANJUNG SELAMAT KEC. PANCUR BATU KAB. DELI SERDANG - Abdurrozaq Hasibuan; Nurul Adina; Fitri Handayani; Suhail Harahap (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
Rice is a food commodity that has a strategic role from both the producer and consumer side. The general objective of the research conducted is to find out whether there is a health impact that arises on the respiration of rice factory workers and the specific objective of this research is to prove the correctness of a theory. and problem solving, from this research will find out whether the theory or methodology is still relevant or not, to be considered as workers, to take better care of their health while working, to add insight and knowledge for researchers and readers. The research method used is qualitative. Based on the results and discussion Based on the observations that have been made, most of the workers in each rice mill have a smoking habit, where smoking habits can cause changes in the structure and function of the respiratory tract and lung tissue so as to accelerate the decline in lung function. Most of the workers also do not use personal protective equipment masks so that rice dust will be more easily inhaled by workers which results in impaired lung function capacity. Impaired lung function can be identified by indicators of decreased lung capacity values, occurring in rice mill workers when compared to non-rice mill workers.